A Radical Access to CF3- and SF5-Containing Dihydrobenzofurans and Indolines - Desroches, Justine; Gilbert, Audrey; Houle, Camille; Paquin, Jean-François (Synthesis, 2017)
The synthesis of 3-(2,2,2-trifluoroethyl)-2,3-dihydrobenzofurans, 3-(2,2,2-trifluoroethyl)indolines, 3-[(pentafluorosulfanyl)methyl]-2,3-dihydrobenzofurans, and 3-[(pentafluorosulfanyl)methyl]indolines using an intramolecular reductive radical cyclization from readily available acyclic precursors is reported. The CF3- and SF5-containing heterocycles are obtained in moderate to excellent yields. Notably, this transformation represents the first example of an aryl radical addition to a SF5-containing alkene. Finally, the possibility of oxidation of some of the products generated to benzofurans and indoles is shown.
Keywords: heterocycles; fluorine; radical reaction; pentafluorosulfanyl; trifluoromethyl; dihydrobenzofurans; indolines